2019
DOI: 10.3390/su12010318
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment Using Economic Value Added

Abstract: Sustainability assessments should be based on financial and non-financial indicators. To describe the financial situation of companies and to calculate the actual economic profit of a company, the Economic Value Added methodology appears as a suitable solution. The aim of the paper is to apply the Economic Value Added methodology to real-life corporate data and present the company’s value through a case study. This study is based on information that was gathered through an extensive literature review (research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
(55 reference statements)
0
14
0
1
Order By: Relevance
“…Recent research that is based on the use of EVA as a performance measurement tool has resulted in analyzes being performed on a single company (Wang and Yang 2014;Ion and Man 2019;Jankalová and Kurotová 2020;Novyarni and Ningsih 2020;Radneantu et al 2010) or in sample-level analyzes (Pavelková et al 2018;Geng et al 2021). From the point of view of the analyzed field of activity, these studies focused on various fields, such as: tourism and hotel industry (Trandafir 2015;Geng et al 2021), construction (Horak et al 2020) oil industry (Wang and Yang 2014), steel industry (Ion and Man 2019), banking industry (Owusu-Antwi et al 2015), IT sector (Radneantu et al 2010), and the sale of spare parts (Jankalová and Kurotová 2020). The conclusions of this research are very diverse.…”
Section: State Of the Art Regarding Evamentioning
confidence: 99%
“…Recent research that is based on the use of EVA as a performance measurement tool has resulted in analyzes being performed on a single company (Wang and Yang 2014;Ion and Man 2019;Jankalová and Kurotová 2020;Novyarni and Ningsih 2020;Radneantu et al 2010) or in sample-level analyzes (Pavelková et al 2018;Geng et al 2021). From the point of view of the analyzed field of activity, these studies focused on various fields, such as: tourism and hotel industry (Trandafir 2015;Geng et al 2021), construction (Horak et al 2020) oil industry (Wang and Yang 2014), steel industry (Ion and Man 2019), banking industry (Owusu-Antwi et al 2015), IT sector (Radneantu et al 2010), and the sale of spare parts (Jankalová and Kurotová 2020). The conclusions of this research are very diverse.…”
Section: State Of the Art Regarding Evamentioning
confidence: 99%
“…They stated that these costs can be reduced through adequate reporting, as Lemma et al [44] also demonstrated in the example of South Africa. Likewise, Jankalová and Kurotová [45] combined the EVA indicator with non-financial indicators on the basis of a case study, with the aim of comprehensively evaluating the business, in particular with regards to the sustainability of its activities. This approach can be found relatively frequently in current research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They need to consider the assumed risk, the dividends paid and the stock price increase in the cost of equity expected for the given investment. All of these deductions (except for the tax deduction) can be summarized in the WACC (Jankalová & Kurotová, 2019). In other words, it can be seen as the excess in the WACC coming from an investment.…”
Section: Economic Value Addedmentioning
confidence: 99%
“…This is why EVA is commonly used, nowadays, as a performance index for defining the compensations of managers and groups of employees (Kleiman, 1999). To describe the financial situation of any company and to calculate the value that was generated, the EVA methodology can be adopted as a suitable solution (Jankalová & Kurotová, 2019). Therefore, EVA is recognized as an important tool for performance measurement and management all over the world, particularly as a component of corporate strategy in advanced economies (Sharma & Kumar, 2010).…”
Section: Economic Value Addedmentioning
confidence: 99%